Integrated Model of Water Infrastructure Development for Water Resources Sustainabilitu (Case Study in Tual City, Indonesia) - Marpaung, Melva Eryani; Kusnoputranto, Haryoto; Soesilo, Tri Edhi Budhi; Ahmad, Mubariq (Journal of Ecohumanism, 2024)
BACKGROUND AND OBJECTIVES: Development in Indonesia which is emphasized on the large island/land areas in the Western Region of Indonesia, has resulted in the underdevelopment of the coastal areas and islands in the Eastern Region of Indonesia. Thus, the welfare and economic conditions of the people in the Eastern Region of Indonesia are lower. Development activities oriented in mainland areas or large islands also have the potential to threaten development sustainability, especially in environ-mental aspects. This research aimed to build an integrated model for water infrastructure de-velopment. METHODS: This study used a quantitative approach by collecting and analyzing data through questionnaires and used dynamic system analysis to build an integrated water infrastructure model. FINDINGS: The results of the study found that environmental degradation that occurred in Tual City was caused by high economic activity around the port of Tual, water supply conditions for the people in the exploitative small island of Tual City, as well as pollution and degradation of the soil quality around the residential area of Tual City. CONCLUSION: The clean water infrastructure integration model with rainwater harvesting and artificial reservoirs can save water purchase costs and increase water supply availability to promote sustainability without causing environmental degradation.